Magnitude of Work-Related Musculoskeletal Disorders and its Associated Factors Among Computer User Bankers in South Gondar Zone, Northwest Ethiopia, 2021 - Biruk Demissie; Chalachew Yenew; Alebachew Amsalu; Getachew Yideg Yitbarek; Nega Dagnew Baye; Gashaw Walle; Sintayehu Asnakew; Binyam Minuye; Fitalew Tadele Adimasu; Anemut Tilahun Mulu; Ermias Sisay; Fentaw Teshome Dagnaw; et al. (SAGE Publishing, 2022)
Introduction: Musculoskeletal disorders (MSDs), which are the leading cause of workplace health problems; affect workers, employers, and society as a whole following direct and indirect cost. Bankers are expected to perform at computer workstations for long periods of time. As a result, they are at risk of developing musculoskeletal disorders. Hence, this study intends to assess magnitude of work related musculoskeletal disorders and its predictors among computer user bankers in this study area. Material and methods: Institutional based cross-sectional study was conducted from September to December 2021. A total of 422 private and Public own computer user bankers were participated. Simple random sampling technique was used to select the study participants. Binary logistic regression model was used to investigate the relationship between dependent and independent variables. P value less than .05 at 95% CI was considered as a significant association between dependent and independent variables. Result: Overall, 245 (58.8%) of computer-user bankers were suffered work-related musculoskeletal disorders in the previous 12 months. Aged 30 and above [AOR:6.5 (1.7-24.6)], no regular physical exercise [AOR: 6.03 (2.2-16.3)], not received ergonomics training [AOR: 5.46 (2.2-13.1)] and working in awkward posture [AOR: 8.76 (2.9-25.9)] were significantly associated to work related musculoskeletal disorders in the previous 12 months. Conclusion: The magnitude of musculoskeletal disorders among computer user bankers was high. Implementing proper working posture, regular physical exercise, avoiding prolonged use of computer and receiving ergonomics training will reduce the burden of musculoskeletal disorders among computer user bankers. The implications of the findings enhance the need for training supervision, cascading tasks taking the age of workers in to account, sustained supply of work station materials and promoting physical exercise by banks to their workers uninterruptedly.